Adequação de calçadas e travessias às condições mínimas de acessibilidade : um procedimento para estimativa de custos de serviços e obras - Guerreiro, Pablo José Martinelli (Universidade Federal de São Carlos, 2008)
Abstract: This study presents a procedure used to determine the cost of adapting sidewalks and urban crossings through cost quantification of work needed to repair or rebuild a sidewalk segment and to adapt its crossing. The necessary work was estimated in accordance with Calçada Cidadã standards, a project elaborated by the city administration of Vitória, ES, Brazil. The sidewalk quality was assessed by determining the level of required work according to procedures and recommendations described in Ferreira & Sanches (2005). Based on these sidewalk and quality assessment models a computer program prototype was developed to assess the quality of public spaces and to determine the necessary amount of work, and its corresponding cost, to make them more accessible. In order to test the prototype and assess its viability a case study was carried out in São Carlos, SP, Brazil. It assessed the conditions of a sidewalk segment of this city s downtown streets and determined the cost of improvement work needed to make it accessible to all pedestrians.
Keywords: Qualidade nas calçadas; Cadeira de rodas; Qualidade de serviço - adaptação; Construção civil estimativas; Mobility; Accessibility; Evaluation of the quality of the roadways; Broken accessible; Adaptation costs; ENGENHARIAS